The Effect of Risk Readiness and Perception of Values on Decisions of Using Motorcycle with the User's Involvement as Intervening - Aslamia Rosa; Achmad Widad; Islahuddin Daud (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
This study aims to reveal how the role of Risk readiness, perceptions of values that influence the decision to use a motorcycle through the user's involvement. The population in this study were motorcycle users in Palembang city who had at least used it for six months. This study uses a sample of 201 people with data analysis techniques using Structural Equation Modelling (SEM). Based on the results of data analysis carried out, it is known that consumer involvement is not an intervening variable between Risk readiness and consumer decisions, and nor between consumer perceptions and consumer decisions. On the contrary, both exogenous variables actually influence consumer decisions directly. Consumer perceptions also do not require deep thinking but directly have an impact on consumers to decide using a motorcycle